A New Graphene Quantum Dot Sensor for Estimating an Antibiotic Concentration. (10th January 2018) - Ahamed, N.N.N.; Fan, W.; Schrlau, M.; Santhanam, K.S.V.
ABSTRACT: The graphene quantum dots (GQD) are unique for several different applications especially in the area of sensors as they provide a platform for large surface area on which sensing material can be attached. We wish to report here a new analytical method for sensing ciprofloxacin (CPFX) antibiotic using GQD electrode in differential pulse voltammetry (DPV) which is based on the ferric ion interaction with CPFX. Ferric ion undergoes a well defined one electron reduction at GQD electrode in DPV at Ep =0.310 V vs saturated calomel electrode (SCE) with a peak width of 0.100 V. When nanomolar to micromolar concentrations of CPFX is present in the electrolytic bath, the ferric ion reduction peak decreases with the appearance of three new peaks at Ep I =0.200 V, Ep II =0.050 V and Ep III = -0.085V. The three peaks are attributed to the three stages of binding of CPFX with three positive charges of ferric ion. The decrease of the ferric ion peak at 0.31 V is proportional to the concentration of CPFX. Due to large surface area of GQD, the CPFX bound ferric ion shows enhanced currents in comparison to glassy carbon electrode. The sensor is fabricated by depositing GQD containing known concentration of ferric ion. The sensor response to different concentrations of CPFX is measured for an analytical purpose.